2016
DOI: 10.1016/j.jspd.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Surgical Site Infection With VEPTR at Eight Centers: A Retrospective Cohort Analysis

Abstract: III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Such a discrepancy is very confusing. Garg et al [ 37 ] identified only wound complications following VEPTR implant or revision surgeries. If so, adding implant, alignment, and medical-related complications, the final percentage of complications should be expected at a much higher level.…”
Section: Discussionmentioning
confidence: 99%
“…Such a discrepancy is very confusing. Garg et al [ 37 ] identified only wound complications following VEPTR implant or revision surgeries. If so, adding implant, alignment, and medical-related complications, the final percentage of complications should be expected at a much higher level.…”
Section: Discussionmentioning
confidence: 99%
“…VEPTR hardware infections have been reported in the literature to occur in 1.5 to 24 percent of patients. 2,11,12,[23][24][25] Theoretically, muscle flaps have demonstrated resilience when used over an infected wound bed, [26][27][28][29] because they have better bactericidal activity than random skin and fascial flaps as a result of their superior perfusion facilitating delivery of antibiotics, nutrients, leukocytes, and other inflammatory response mediators to the devitalized area. 26,28 Muscle flaps demonstrate rapidly increasing blood flow to the muscle within the first 24 hours, whereas fascial flaps demonstrate a slow gradual increase over several days.…”
Section: Surgical Factorsmentioning
confidence: 99%
“…Since the year 2000, the reported risk of SSI in pediatric spine surgery ranges from 0% to 26.3% in the USA. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Most of these studies have found that patients with non-idiopathic deformities, including cerebral palsy (CP), are at increased risk of SSI compared with those with idiopathic etiologies. 1,3,4,16 Treatment of SSI entails surgical irrigation and debridement of the wound (often multiple), long-term antibiotic treatment/suppression, and possibly implant removal or revision.…”
mentioning
confidence: 99%
“…Surgical site infection (SSI) after pediatric spine surgery is a well‐recognized complication. Since the year 2000, the reported risk of SSI in pediatric spine surgery ranges from 0% to 26.3% in the USA 1–18 . Most of these studies have found that patients with non‐idiopathic deformities, including cerebral palsy (CP), are at increased risk of SSI compared with those with idiopathic etiologies 1,3,4,16 .…”
mentioning
confidence: 99%